PELATIHAN PENGEMASAN DAN PEMASARAN PRODUK UNGGULAN IKAN ASAP DI DESA PURNAMA KECAMATAN PUREMAN KE PASAR GLOBAL - Nehemia Fanpada; Maryios Abia Tekamaki, Nyoman Lukas Mantaon, Julrian Lazarus Tema, Agnes Maukaling, Rismelia V Mautu (JOURNAL OF COMMUNITY DEDICATION, 2025)
The fish smoking business in Purnama Village has considerable potential for continued growth. Smoked fish processing is carried out traditionally by the local community, using Kusambi wood charcoal. Meanwhile, packaging is still done simply using plastic bags, so the fish produced cannot last long, resulting in local communities not being able to market outside the region or widely, but still limited to local marketing and to meet daily needs. Based on these constraints, it is very important to conduct training on packaging and global marketing methods through community service activities in Increasing Smoked Fish Production through training on storing and packaging Smoked Fish Processing so that it does not spoil quickly and can last longer. This community service activity is carried out through Community Learning and Assistance Activities (KBPM) conducted by Tribuana Kalabahi University to provide knowledge on packaging smoked fish to make it attractive, long-lasting or not easily damaged so that it can be marketed globally. The target output of this community service activity is publication in a national journal with ISSN. The training methods in this activity are team formation, formulation of objectives, identification of target communities, collection and analysis of needs, and determination of priority solutions to problems. The activity is planned in two stages for two days. The first stage is the smoking process, and the second stage is an introduction to vacuum equipment and training in vacuum-packaging fish. This activity aims to improve the community's knowledge and skills in the smoked fish business, equip them with the skills to use vacuum equipment, and effectively package fish, thereby increasing product value. Smoked fish entrepreneurs can also increase their competitiveness in the market, which can then be used as a source of income.